2017
DOI: 10.1073/pnas.1621359114
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling promotes JNK-dependent cell migration

Abstract: Overwhelming studies show that dysregulation of the Hippo pathway is positively correlated with cell proliferation, growth, and tumorigenesis. Paradoxically, the detailed molecular roles of the Hippo pathway in cell invasion remain debatable. Using a Drosophila invasion model in wing epithelium, we show herein that activated Hippo signaling promotes cell invasion and epithelialmesenchymal transition through JNK, as inhibition of JNK signaling dramatically blocked Hippo pathway activation-induced matrix metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 56 publications
4
63
0
Order By: Relevance
“…Expression of puc can prevent ptc>dCskRNAi cells from spreading at the A/P boundary (Vidal et al, 2006). JNK activity is also needed for ykiRNAi cells to invade across the wing disc A/P boundary, and co-expression of bsk DN and ykiRNAi blocks this invasion (Ma et al, 2017). Consistent with the role JNK in BCE regulation, blocking JNK signaling by bsk DN expression can prevent ykiRNAi cells from being extruded to the basal side of the wing epithelia (Fig.…”
Section: Jnk Signaling Mediates Hpo-activation-induced Cell Extrusionsupporting
confidence: 52%
See 2 more Smart Citations
“…Expression of puc can prevent ptc>dCskRNAi cells from spreading at the A/P boundary (Vidal et al, 2006). JNK activity is also needed for ykiRNAi cells to invade across the wing disc A/P boundary, and co-expression of bsk DN and ykiRNAi blocks this invasion (Ma et al, 2017). Consistent with the role JNK in BCE regulation, blocking JNK signaling by bsk DN expression can prevent ykiRNAi cells from being extruded to the basal side of the wing epithelia (Fig.…”
Section: Jnk Signaling Mediates Hpo-activation-induced Cell Extrusionsupporting
confidence: 52%
“…2B). It is known that activated Hpo plays a role in cell-migration (Ma et al, 2017). yki-depleted cells migrated across the A/P boundary and extruded basally, and this cell migration was suppressed by ban.…”
Section: Activated Hpo Pathway Induces Cell Extrusion In the Drosophimentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been hypothesized that phosphorylated JNK acts as an inducer of Drp1 activation [27] and that Yap has the ability to regulate JNK phosphorylation [25]. To determine whether Yap influences Drp1-mediated fission via JNK, we first assessed changes of JNK.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recent studies have indicated that the Hippo-pathway facilitates mitochondrial function via Bcl-xL [24], demonstrating a possible relationship between Yap and cytoplasmic mitochondria. Furthermore, accumulating evidence has described the regulatory action of Yap on JNK [25, 26]. Thus, together with the confirmed role of JNK in initiating mitochondrial fission [27], these findings raise the possibility that Yap may govern mitochondrial fission via JNK.…”
Section: Introductionmentioning
confidence: 89%